Front-End Governance of a Major Public Project in Laos: A Conceptual Framework for Ensuring the Right Concept - Mackhaphonh, Nikhaphone; Jia, Guangshe; Xu, Qixiong (Frontiers in Built Environment, 2021)
Major public projects in Laos are facing with multiple challenges, including project identification, and its decision-making. Generally, an identification is an important key identifying the potential needs and requirements for achieving the development goal. However, the process was developed without a formal framework and assurance tools that have been criticized for negative social and environmental consequences as “white elephant projects” in over the past few years. Considering this context, the study aims to develop a conceptual framework to navigate an alternative solution for the right project. Based on contextual analysis and systematic literature review, the proposed framework provided the process of concept development and its assurance that could be systematically developed in a cause-effect chain of needs. The findings indicate areas for reflect new insights of both strategic performance and governance system, it had reform of the decision-making process in providing new knowledge, new rules, and procedures for the effective governance.